2005
DOI: 10.1016/j.jcrs.2005.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Cyanoacrylate repair of laser in situ keratomileusis corneal flap perforation by a snake bite

Abstract: A 30-year-old man who had laser in situ keratomileusis (LASIK) for myopia 1 year earlier developed a corneal perforation in the left eye from a boa constrictor. The patient presented to the emergency room, and a small corneal perforation just outside the visual axis was diagnosed within the LASIK flap. Cyanoacrylate adhesive was used to close the corneal perforation. The patient went on to full visual recovery with an uncorrected visual acuity of 20/20. This is the first reported case of a penetrating corneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…24 Cyanoacrylate adhesive was reported in a case of corneal perforation after LASIK. 25 Diffuse lamellar keratitis is a significant concern after LASIK. Another is epithelial ingrowth, and several surgeons report success using alcohol (30% to 100%) to destroy residual interface epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…24 Cyanoacrylate adhesive was reported in a case of corneal perforation after LASIK. 25 Diffuse lamellar keratitis is a significant concern after LASIK. Another is epithelial ingrowth, and several surgeons report success using alcohol (30% to 100%) to destroy residual interface epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Direct inoculation of venom into the eye has been known to cause globe necrosis, keratomalacia and uveitis, often ending up requiring evisceration or enucleation [9,10]. Direct ocular trauma from the bite of a non-venomous Boa constrictor has also been reported [11][12][13]. This is the first ever reported case of ocular trauma inflicted by a python species.…”
Section: Discussionmentioning
confidence: 91%
“…The range of complications from snake bites to the eye is largely dependent on the extent of damage and whether the snake is venomous or nonvenomous. This is the first reported case of a wild snake in North America directly biting the eye, as the four cases of penetrating globe injuries reported thus far in North America have been by pet snakes [1][2][3][4].…”
Section: Introductionmentioning
confidence: 78%
“…Standard of care for nonvenomous site bites elsewhere on the body does not include empiric antibiotics to prevent secondary infections after snakebites, although tetanus prophylaxis should be provided as needed. Of those with reported drug selections (five cases) [1][2][3][14][15], each patient received treatment with a topical fluoroquinolone, although the specific drug of choice varied. Kleinman et al discussed the likelihood of bacterial stomatitis, especially in captive snakes, as a reason for antibacterial therapy in ocular snakebite injuries and found that in the pet Boa constrictor case, cultures from the teeth of the snake showed multiple species of Gram-negative rods [3].…”
Section: Discussionmentioning
confidence: 99%